Determinants of husbands’ involvement in family planning: Evidence from a community-based cross-sectional study in Uttar Pradesh, India - Sanjiv Singh; Arupendra Mozumdar; Abhishek Kumar; Abhishek Gautam; Kaushalendra Kumar Singh; Rajib Acharya (PLoS ONE, 2026)
We argue that the husband’s involvement in family planning (FP) should encompass a larger role such as participation in the joint decision-making on FP and supporting their wives in contraceptive use, rather than just being FP clients. This study assessed husbands’ involvement in decision-making of family size and contraceptive use and examined factors associated with such involvement in two districts of Uttar Pradesh, India among husbands of 1,258 currently married women of reproductive age. The study considered a set of demographic, socio-economic, attitudinal, and programmatic variables to explain the variation in the husbands’ involvement in FP. We have applied latent class analysis to identify classes based on the attitude of husbands towards FP and contraceptive use. Nearly two-thirds (65%) of the husbands are involved in decision-making on family size and over half (56%) of the husbands are involved in supporting their wives’ contraceptive use. Having a positive attitude toward FP and contraceptive use along with media exposure to FP were the most significant determinants for husbands’ involvement in FP to decide family size (AOR = 4.18, 95% CI 2.96–5.88) and support wives’ contraceptive use (AOR = 3.98, 95% CI 2.82–5.61) even after adjusting for the factors like parity, religion, and having a son. The FP program should consider strategies involving husbands with positive attitudes across social and religious groups to popularize FP.